2015
DOI: 10.1245/s10434-015-4455-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Breast Cancer in a Population with Increased Prevalence of Triple-Negative Breast Cancer: Androgen Receptor and ALDH1 Expression in Ghanaian Women

Abstract: Introduction Androgen Receptor (AR) is the most commonly-expressed nuclear hormone receptor in breast cancer and may be a marker of response to targeted anti-androgen therapy, a particularly attractive option in the setting of triple negative breast cancer (TNBC). Gene expression studies suggest that AR-positivity may distinguish a luminal/AR TNBC subtype from mesenchymal, stem cell-like, and basal-like subtypes. Furthermore, frequency of TNBC is 2–3-times higher in African American and African compared to Whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 24 publications
4
21
0
Order By: Relevance
“…Another study evaluated AR expression in Ghanaian BC patients. They found a lower percentage (24%) of AR-positive tumors (defined by ≥10% cutoff) among TN BCs ( 16 ).…”
Section: Discussionsupporting
confidence: 93%
“…Another study evaluated AR expression in Ghanaian BC patients. They found a lower percentage (24%) of AR-positive tumors (defined by ≥10% cutoff) among TN BCs ( 16 ).…”
Section: Discussionsupporting
confidence: 93%
“…Another study examined 147 invasive breast tumors from African patients from Ghana and found an association between the prevalence of ALDH1 expression in TNBC and androgen receptor (AR) expression. 106 AR expressing TNBC cell lines are more sensitive to AR antagonists leading to trials exploring the role of AR antagonists in TNBC. ALDH1 is thus a potential predictive biomarker for AR-targeted therapy in TNBC 107 as well as a likely prognostic marker.…”
Section: Tnbc Biomarkers In the Cell Cytoplasmmentioning
confidence: 99%
“…Heterogeneity exists within MCSCs populations, which have high aldehyde dehydrogenase 1 (ALDH1) activity and increased expression of CD44, a cell surface marker [ 39 ]. There are reports of high expression of ALDH1 in breast tumors in women from African origin [ 40 , 41 ]. We found high ALDH1 expression in all the 3 AA TN breast cancer cells examined and NO treatment significantly reduced the expression of ALDH1 in these cells (Fig.…”
Section: Resultsmentioning
confidence: 99%